An experiment to assess the effects of diatom dissolution on oxygen isotope ratios - Smith, Andrew C.; Leng, Melanie J.; Swann, George E.A.; Barker, Philip A.; Mackay, Anson W.; Ryves, David B.; Sloane, Hilary J.; Chenery, Simon R.N.; Hems, Mike (Wiley, 2016)
Rationale: Current studies which use the oxygen isotope composition from diatom silica (δ18Odiatom) as a palaeoclimate proxy assume that the δ18Odiatom value reflects the isotopic composition of the water in which the diatom formed. However, diatoms dissolve post mortem, preferentially losing less silicified structures in the water column and during/after burial into sediments. The impact of dissolution on δ18Odiatom values and potential misinterpretation of the palaeoclimate record are evaluated.